Small mammals at the Field Station - (:unkn) unknown (My University, 1969)
Ecological studies of small mammals are undertaken for a variety of reasons. Some investigations are conducted to determine their economic relationship to man, since small mammals directly affect his welfare through transmission of diseases and parasites and through destruction of crops, orchards, and forest seedlings. Much research, however, is basic in nature. The primary objectives of such research are to aid in man's quest for knowledge concerning the distributional and population aspects of small mammals. During the summer of 1968, an intensive live-trapping program was begun to determine the status of small mammals, primarily mice and shrews, among the various habitats found at the Cedar-Sauk Field Station.
Keywords: white-footed mouse; red-backed vole; meadow vole; meadow jumping mouse; masked shrew; short-tailed shrew